Rapanui Paddles and the Bountiful Sea - Horley, Paul; Solsvik, Reidar; Ramírez-Aliaga, José Miguel (Waka Kuaka, 2022)
Rapanui paddles used in the eighteenth and nineteenth centuries are unusual in that they are composite; their pararaha ‘blades’ are of a very particular shape that has no parallels on other Polynesian islands. Museum collections contain at least ten paddle blades collected in the late nineteenth century, all of them featuring a longitudinal upright that ends in a rounded bulge. The back side of the blade can be flat, slightly concave or carved with a longitudinal groove. Iconographic analysis of pararaha 21.1D from Museo de La Merced revealed that unusual shapes on both sides of the paddle blade represent stylised depictions of male and female genitalia. Although the back of the paddle, shaped like komari ‘female genitalia’, may be of later development, the prominent phallic upright on the front side of the blade is characteristic of all known pararaha. This iconographic identification suggests that Rapanui paddles, documented since the La Pérouse expedition of 1786, might have been considered to possess special magical powers relating to “fertilisation” of ocean waters during routine paddling, thus ensuring bountiful produce from the sea. The power of the paddle may have been enhanced by inlaid bones or teeth, two examples of which are known among the surviving pararaha and detailed here.